PENDAMPINGAN PEMBERANTASAN BUTA HURUF AKSARA ARAB DALAM AL QUR’AN PADA ANAK MELALUI METODE QIROATI DI DESA CIKLAPA, KECAMATAN KEDUNGREJA, KABUPATEN CILACAP - Rakhmah Nafisah; Nada Yulfani Wulandari; Maghfir Akbar; Siti Maryam; Widji Astuti; Mohammad Habib (Universitas Perjuangan Tasikmalaya, 2023)
The qiro'ati method is a method of reading the Al-Qur'an directly, both makhroj, letters and tajwid, read directly tartil and correctly without introducing the letters, harakat and tajwid first (spelling), the teacher only explains the subject matter (how to read) and give examples of reading tartil and correctly. This method of reading the Koran was only completed in 1963 AD by H. Dahlan Salim Zarkasyi, which consisted of 6 volumes. This book is the result of evaluating and developing the Bagdadiyah rules. This Qiroati method, in general, aims to make students able to read the Qur'an properly and correctly according to the rules of tajwid. Community service activities through assisting the learning of the qiro'ati method for children at TPQ ArRohman aim to ensure that the teaching carried out can run well in accordance with the guidance of the Islamic religion as desired by Allah SWT and Rasulullah SAW through His revelations and treatises. The research that has been carried out aims to determine the Process of Learning Assistance of the Qiro'ati Method for TPQ ArRohman's Children. The approach used in this community service activity includes the qiro'ati method, lectures, and questions and answers. The results of this research show that community service activities carried out by assisting qiro'ati learning for TPQ ArRohman children are as follows: first, increasing the insight and knowledge of the students about the science of recitation and the qiro'ati method. Second, fostering the enthusiasm of students in improving their knowledge of recitation, and third, helping educators in applying the qiro'ati method in learning to read the Al-Qur'an at TPQ ArRohman.